THE PERFORMANCES OF COATED CUTTING TOOLS IN MILLING DAC52 ON SURFACE INTEGRITY - Manan, A.H.; Ibrahim, M.R.; Rafai, N.H.; Latif, A.A. (Journal of Advanced Manufacturing Technology (JAMT), 2021)
Machining of hardened steel in die and mould making has been intensively used in recent years. Various coated carbide tools have been developed to improve the performance, quality and efficiency in machining hardened steel. Now, hardened steel products tend to have poor quality surface finish and cause major loss for the company. The purpose of this research is to investigate the performance of surface roughness of coated cutting tool on steel DAC52 under dry conditions. Machining process was carried out by using CNC milling machine under side milling operation by using three types of coated cutting tools. The measurement of images’ microstructure, white layer and microcrack was done under Optical Microscope. The values of surface roughness were tested using Mitutoyo surface roughness tester while microhardness values were tested by using Vickers microhardness tester. The highest value of surface roughness was found when gold coated cutting tool was milled with DAC52, which is 0.40 µm, while the blue coated cutting tool produced higher length of microcrack which is 50 µm. In conclusion, the blue coated cutting tool is the best tool to be selected as a tool to be machined, because the tool produces less defect such as microcrack or white layer.